PENGEMBANGAN PETA JALAN INFORMATIKA KEHATI DI ORGANISASI RISET HAYATI DAN LINGKUNGAN–BADAN RISET DAN INOVASI NASIONAL (BRIN) - Farid Rifaie; Sjaeful Afandi; Hetty IP Utaminingrum; Uus Khusni; Endah Mardiyani (UIN Sunan Gunung Djati Bandung, 2023)
Biodiversity informatics has been developed for more than 30 years at the Research Center for Biology – Indonesian Institute of Sciences. However, the goal of digitizing all biological specimen data and distributing it to a biodiversity information network has not been achieved. The development of Biodiversity information at the Research Center for Biology was struggled to keep up with the system requirements and rapid technological advancements. Learning from these three decades of experience, a roadmap for the development of biodiversity informatics must be built by taking into account the successes that have been achieved and dismiss all past mistakes. The biodiversity informatics roadmap was made as a reference for system development for the next four years. The development of biodiversity informatics involves all stakeholders who were incorporated into working groups according to their expertise. Each step of database application development is carried out by one of the working groups and supervised by the data mobilization policy working group. In addition to the application of the biological specimen database, the development of this biodiversity informatics also formulates the development of a national taxonomic reference database and a data warehouse as a sharing platform of Indonesian biodiversity data. The whole set of working procedures for the development of biodiversity informatics will be recorded in various documents that are easily understood by parties involved or not involved in the development of biodiversity informatics. It is hoped that this road map for biodiversity informatics will become a benchmark for the future development, so that it can continue to run sustainably in accordance with technological advancements and system requirements.